Structural and chemical aspects of HPMA copolymers as drug carriers - Ulbrich, Karel; Subr, Vladimír (Advanced drug delivery reviews, 2010)
Synthetic strategies and chemical and structural aspects of the synthesis of HPMA copolymer conjugates with various drugs and other biologically active molecules are described and discussed in this chapter. The discussion is held from the viewpoint of design and structure of the polymer backbone and biodegradable spacer between a polymer and drug, structure and methods of attachment of the employed drugs to the carrier and structure and methods of conjugation with targeting moieties. Physicochemical properties of the water-soluble polymer-drug conjugates and polymer micelles including mechanisms of drug release are also discussed. Detailed description of biological behavior of the polymer-drug conjugates as well as application of the copolymers for surface modification and targeting of gene delivery vectors are not included, they are presented and discussed in separate chapters of this issue.
Keywords: nosiče léků; Drug Carriers; Molecular Structure; polymery; Acrylamides; akrylamidy; Polymers; Animals; Humans; Drug Delivery Systems; lidé; zvířata; lékové transportní systémy; molekulární struktura